Perceived Factors Influencing ICT Vendors – Value Added Reseller Partnerships' Satisfaction in South Africa. Issue 1 (5th December 2017) - Hassa, Ishmael; Tanner, Maureen
Abstract: This study explores the perceived factors contributing to relationship satisfaction between Information and Communication Technologies (ICT) downstream supply chain management (SCM) and Vendors and Value‐added Resellers (VARs) in South Africa (SA). The study is qualitative, and relevant experts from both ICT Vendors and VARs were interviewed. The study utilises the Interaction Approach (IA) as the theoretical lens to analyse the data. The themes resulting from the thematic analysis are Power/Dependence (IA), Cooperation, Closeness (IA) and Expectation (IA). As part of the findings, the IA model is also extended to reflect interesting and important factors that emerged from the study. The findings extend the environment variable within IA for the South African context. Unique environment issues are exposed, such as Broad‐Based Black Economic Empowerment (B‐BBEE) and Currency that have a bearing on relationship satisfaction in the ICT industry. This inquiry is intended to encourage discussions between stakeholders and to be a catalyst for further research. The results from these findings could aid transparent cooperation and collaboration between ICT industry partners and stakeholders in SA (customers, government, etc.).